Compensation for professional damages on the basis of civil liability - a comparative study - - Saad Al-Jabbar, teacher Sawsan (The college of law and political science journal, 2023)
Compensation for professional damages that it exports due to economic factorsthat it exports due to economic factors caused by Social Security No. 39 of 1971,commenting on the image of the idea of the imam of the judiciary to compensatefor damages, damages, general paragraphs, general paragraphs, study of generalfoundations, study of legal foundations, study Legal disability, economic study